Travel booking management system for Sriamera Holidays / Muhammad Faqrul Ariffin Mohd Fadil - Mohd Fadil, Muhammad Faqrul Ariffin (2022)
Major problem of the booking process particularly in travel agency is data management. Data Management in the pre booking phase are cost-sensitive to change and time-sensitive to handle especially in the holiday seasons. Every data recorded are bounded to fee if there are needs to change and only have a limited time window before it is unchangeable. This project is about a management information system, Travel Booking Management System (TBMSSH) which was developed to accommodate the booking process of Sriamera Holidays. The main purpose of this project was to solve the current problems that occurs in the current process of conducting, receiving and handling booking between Sriamera Holidays’s admin and its customers. The problems were identified and solved since the existing booking process are not organized and cannot be managed in one platform due to the company receiving booking via emails and calls. Data and information handling using emails and calls is an invitation for human error, data redundancy and data lose to occur. Any changes that need to be made had to go through hassle process that cause time and resource wasted. This system was developed using an adapt-waterfall model. There are three users that can use the system which are Sriamera Holidays’s admin, its customers and its ground agents. All user’s requirement and system functionalities were fulfilled successfully. Despite that, there are weaknesses and limitation that TBMSSH had to suffer such as less attractive user interface design, no additional functionalities and limited ground agent functionalities. In conclusion, there are recommendation, correction and the possible improvement that can be made to the system.